General Features of the Metallic Corrosion in Raw Crude Oils - Aluvihara S.; Premachandra J. K. (Журнал інженерних наук)
Raw crude oils are mainly composed of various hydrocarbons while having trace amounts of corrosive compounds such as sulphur compounds, naphthenic acids, and salts. In the existing research, there were expected to investigate the impact of such corrosive properties on the corrosion of seven different types of ferrous metals. As the methodology, the major corrosive properties of selected two different types of crude oils and the chemical compositions of seven selected metal types were measured and analyzed by the standard methodologies and recommend instruments. The corrosion rates of such metals were determined by the relative weight loss method after certain immersion time periods simultaneously with the microscopic analysis of corroded metal surfaces. In addition, the decayed metallic elemental concentrations from metals into crude oils were analyzed by the atomic absorption spectroscopy (AAS) and the impact of the corrosion on the initial hardness of metals were measured by the Vickers hardness tester. As the results and outcomes of the entire research that there observed relatively lower corrosion rates from stainless steels with at least 12 % of chromium and some amount of nickel, higher corrosive impact from salts on the metallic corrosion, formations of FeS, Fe2O3, corrosion cracks and pitting on the metal surfaces, decay of copper and ferrous from some of metals sometimes in significantly and small reductions of the initial hardness of most of metals due to the corrosion.